"Divide and conquer". Anti-racist and community organizing under austerity. Issue 16 (10th December 2020) - Harries, Bethan; Byrne, Bridget; Garratt, Lindsey; Smith, Andy
ABSTRACT: This paper examines the effects of austerity on anti-racist and community organizing. We focus on three key shifts: changes to public funding, the push to entrepreneurialism and the mainstreaming of Equalities legislation. The paper contributes to critical understandings of the changing relationship between civil society and the state and the challenges this creates for working against racism. We highlight how austerity acts as an alibi to further diminish race as a policy concern. Organizations and activists are encouraged to act as entrepreneurs and confront each other as competitors, rather than allies in a political struggle. This leads to a very real sense that solidarities are being deliberately ruptured in order to "divide and conquer" and diminish collective organizing capacity. We illustrate how this is compounded by the cumulative affective consequences of austerity measures, often at considerable costs in terms of a broader collective agenda.